Effectiveness of Hydromulching to Reduce Runoff and Erosion in a Recently Burnt Pine Plantation in Central Portugal. (14th August 2013) - Prats, Sérgio Alegre; Malvar, Maruxa Cortizo; Vieira, Diana Catarina Simões; MacDonald, Lee; Keizer, Jan Jacob
Abstract: Forest fires can greatly increase runoff and surface erosion rates. Post‐fire soil erosion control measures are intended to minimize this response and facilitate ecosystem recovery. In a few recent cases, hydromulch has been applied, and this consists of a mixture of organic fibers, water and seeds. The objectives of this research were to (i) analyze the effectiveness of hydromulch in reducing post‐fire runoff and sediment production and (ii) determine the underlying processes and mechanisms that control post‐fire runoff and erosion. After a wildfire occurred in August 2008, 14 plots ranging in size from 0·25 to 10 m 2 were installed on a 25 degree slope in a burnt pine plantation that had also been subjected to salvage logging. Half of the plots were randomly selected and treated with hydromulch. One of two slope strips adjacent to the plots was also hydromulched and used for monitoring some soil properties. Measurements made in each of the first 3 years following the wildfire included (i) the plot‐scale runoff volumes and sediment yields; (ii) soil shear strength, soil moisture, and soil water repellency; and (iii) surface cover. The hydromulch reduced overland flow volume by 70% and soil erosion by 83%. The decrease in runoff was attributed to the increase in soil water retention capacity and the decrease in soil water repellency, whereas the reduction in soil erosion was initially attributed to the protective cover provided by the hydromulch and lately to an enhanced vegetative regrowth in the third year after burning. Copyright © 2013 John Wiley & Sons, Ltd.